Kaltim Post Editorial Strategy in Maintaining the Existence of the Media Business in the Digital Era - Sarinah Sarinah; Nur Alim Djalil; Sadly Abdul Djabar (Journal La Bisecoman, 2023)
Currently, print media is starting to be abandoned because most people have digital media as a place to find news. This is felt by Kaltim Post which indirectly requires it to adapt to changes in behavior in society in reading news today. For this reason, this research aims to determine the Kaltim Post Editorial Strategy in Maintaining Existence in the Digital Media Era. This research uses qualitative research methods with data collection techniques in the form of interviews. In data collection, this research had five key informants. The results obtained in this research are that Kaltim Post is proven to have used a media conversion strategy to be able to maintain their existence in the current digital era.